Influence of poly(lactic acid) layer on the physical and antibacterial properties of dry bacterial cellulose sheet for potential acute wound healing materials - Yee, Foong Choi; Anwar Hamzah, Mohd Syahir; Abd Razak, Saiful Izwan; Saidin, Syafiqah; Mat Nayan, Nadirul Hasraf (Springer, 2018)
Dry bacterial cellulose nanofiber (BC) sheet coated with poly(lactic acid) (PLA) was developed and characterized towards acute wound healing applications. This new approach of PLA coating on BC revealed enhanced physical and antibacterial properties. Commercial BC sheets originated from the manufacturing of nata de coco jelly were dried and coated with the PLA at various concentrations of 2, 4, 6, 8, 10 and 12 % w/v for the purpose of improving the mechanical properties and followed by loading of antiseptic such as benzalkonium chloride (BAC). PLA has been proposed for the use of coating materials at a concentration of 8 %, the biocomposite sheet started exhibiting a low moisture uptake, prolonged swelling in simulated wound fluid solution and high tear (9.17 Nm2 /kg) and burst indices (32.5 kPa·m2 /g). The 8 % PLA coating revealed porous fiber-like morphology as observed under scanning electron microscope. Therapeutic loading capacity of the BC/8 PLA was substantially higher than the pristine BC. Furthermore strong antimicrobial activities against Staphylococcus aureaus and Escherichia coli were observed for the BC/8PLA biocomposite film. These reports were clearly suggestive of the fact that synthetic biodegradable polymers, such as PLA, may be exploited for the synergistic combination with BC for antimicrobial and acute wound management. This new and modified fiber source material could reduce the dependency on plant based cellulose for more demanding biomedical applications such as wound healing materials, vascular graft, cartilage replacement, drug delivery and tissue engineering.